1999
DOI: 10.1038/sj.jhh.1000722
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, hypertension and correlates in urbanised workers in Ibadan, Nigeria: a revisit

Abstract: To provide an update on blood pressure (BP) levels and hypertension correlates in urban workers in Ibadan, Nigeria, we administered a questionnaire to, and measured the BP in, 608 men and 309 women, age range 18-64 years. Systolic BP (SBP) rose in men and women after the age of 25, but the rise in diastolic BP (DBP) started earlier dropping in women only after the age of 44. SBP and DBP were higher in men than women (P Ͻ 0.001). The prevalence of hypertension was 9.3% in the population, being 10.4% in men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 18 publications
9
75
7
Order By: Relevance
“…Alcohol consumption was similarly found not to impart any excess risk on the MHT group, although it is a clear risk factor for hypertension in Nigerians. 24,26 Oral contraceptives were infrequently used, and analgesic use was not evaluable because of unreliable reporting. Oral contraceptives use was not associated with MHT, in agreement with a recent study, which showed that MHT was not related to contraceptives use, 27 but not in agreement with others.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption was similarly found not to impart any excess risk on the MHT group, although it is a clear risk factor for hypertension in Nigerians. 24,26 Oral contraceptives were infrequently used, and analgesic use was not evaluable because of unreliable reporting. Oral contraceptives use was not associated with MHT, in agreement with a recent study, which showed that MHT was not related to contraceptives use, 27 but not in agreement with others.…”
Section: Discussionmentioning
confidence: 99%
“…Using the revised cut-off of 140/90 mmHg, a revised prevalence rate of 17-20 % has been reported. 11 In another population-based survey, a prevalence rate of 14.5 % was observed. 12 In a meta analysis of studies on prevalence of hypertension in Nigeria, prevalence rates ranges from 12.4 to 34.8 % among adults in Nigeria.…”
Section: Introductionmentioning
confidence: 94%
“…Adjusting these, with the cut-off point of 140/90mmHg, these results would lead to a current prevalence rate of 17 to 20% (7.8million) 10 It is recommended from this study, that as much as practicable, hypertensive patients be evaluated with Doppler echocardiogram in order to detect the early effects of hypertension on the heart, especially as represented by diastolic dysfunction, with a view to affecting the management outcome.…”
mentioning
confidence: 99%